2020
DOI: 10.3389/fmicb.2020.567235
|View full text |Cite
|
Sign up to set email alerts
|

Regional Variation of Extended-Spectrum Beta-Lactamase (ESBL)-Producing Enterobacterales, Fluoroquinolone-Resistant Salmonella enterica and Methicillin-Resistant Staphylococcus aureus Among Febrile Patients in Sub-Saharan Africa

Abstract: Background: Antimicrobial resistance (AMR) thwarts the curative power of drugs and is a present-time global problem. We present data on antimicrobial susceptibility and resistance determinants of bacteria the WHO has highlighted as being key antimicrobial resistance concerns in Africa, to strengthen knowledge of AMR patterns in the region. Methods: Blood, stool, and urine specimens of febrile patients, aged between ≥ 30 days and ≤ 15 years and hospitalized in Burkina Faso, Gabon, Ghana, and Tanzania were cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…To date, there are no co-ordinated antimicrobial stewardship activities in Gabon. The routine and clinical data on microbiological resistance from the Lambaréné referral hospital show increasing AMR rates [ 7 , 12 ]. We hypothesised that there is a gap in knowledge of HCW about AMR.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there are no co-ordinated antimicrobial stewardship activities in Gabon. The routine and clinical data on microbiological resistance from the Lambaréné referral hospital show increasing AMR rates [ 7 , 12 ]. We hypothesised that there is a gap in knowledge of HCW about AMR.…”
Section: Introductionmentioning
confidence: 99%
“…Other potential risk factors include travels to high-risk areas for AR , nutrition (28,29), health status (21,25), and occupation (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). However, most of the studies examining potential risk factors focus on high-risk populations such as travelers (8,10,14,18,20,25,26,46), healthcare workers and patients (39,44,45,47,48), swimmers (49)(50)(51), farmers (32)(33)(34)(35)37,38,40,42,43), and slaughterhouse workers (31), and often using small convenience samples of e.g. students (16,17,…”
Section: Introductionmentioning
confidence: 99%
“…Study on the emergence and epidemiology of AMR in S. aureus and spread of methicillin resistant S. aureus (MRSA) in Sub-Saharan Africa (SSA) has intensified [7,8] but data OPEN ACCESS from resource-poor regions remains sparse. In Uganda, AMR phenotyping of S. aureus strains derived from symptomatic and apparently healthy humans and livestock has suggested that resistance to different and multiple antibiotics, including methicillin is prevalent [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…aureus and spread of methicillin resistant S. aureus (MRSA) in Sub-Saharan Africa (SSA) has intensified [7, 8] but data from resource-poor regions remains sparse. In Uganda, AMR phenotyping of S.…”
Section: Introductionmentioning
confidence: 99%